Improving the current regulatory issues concerning training ships for maritime institutions: The South Korean case - Junghwan Choi; Sangil Lee; Soyeon Kim (Asian Journal of Shipping and Logistics (AJSL), 2022)
Unlike commercial vessels, training ships have the unique purpose of providing students attempting to become ships' officers with the onboard training education referred to in the International Convention on Standards of Training, Certification and Watchkeeping for Seafarers (STCW code). More than 100 people, including students, are usually aboard these internationally seagoing vessels. Despite training ships requiring strict safety management to prevent maritime accidents and protect lives, they are excluded from the application of key international rules and regulations concerning the safety of these ships due to an ambiguous legal status. Furthermore, there is no comprehensive safety management system at the central governmental level over training ships as they are operated by individual maritime institutions despite them being national property. Against these backgrounds, this research analyses current regulatory issues of training ships at the IMO level and the domestic level by referring to South Korean case. This research conducts a doctrinal legal study to understand the current legal status of training ships the application limits of the IMO regulatory instruments. The research concludes by referring to the necessity of the development of training ships Code to enhance he safety of training ships in the future.
Keywords: 650; Government Ship; ISM Code; Non-commercial Ship; SOLAS; Training Ship